Alternative agrifood movements patterns of convergence and divergence - Rivera-Ferre, Marta; Constance, Douglas; Renard, María Christine (Bingley, U.K. : Emerald, 2014)
This volume explores the issues of convergence and divergence in alternative agrifood movements through a theoretical and empirical engagement of the topic by notable agrifood researchers from Europe, North America and South America. It probes the degree to which the numerous alternative agrifood movements that have emerged in recent years in response to the legitimation crisis of conventional agriculture have converged around a central alternative thesis or pursued divergent paths of development. Some alternative agrifood movements represent radical critiques of conventional agriculture that challenge the existing system while other movements engage in reformist and accommodative approaches that are viewed as complimentary. The book begins with chapters that enhance the theoretical discussions on the pathways and obstacles to convergence followed by empirical case studies on organics, food sovereignty, landless workers, alternative food systems, and food policy councils.
The discourse on alternative agrifood movements / Douglas H. Constance ... [et al.] -- Divergence and convergence in alternative agrifood movements : seeking a path forward / Patricia Allen -- Alternative agrifood movements and social change / Marie-Christine Renard -- Building alliances for food sovereignty : La Vía Campesina, NGOs and social movements / Annette Aurélie Desmarais, Marta G. Rivera-Ferre, Beatrice Gasco -- Food sovereignty and struggle for land : the experience of the MST in Brazil / Débora Franco Lerrer, Leonilde Servolo de Medeiros -- Food sovereignty and agroecology in the convergence of rural social movements / Peter M. Rosset, María Elena Martínez-Torres -- The transformative agrifood movement in Catalonia : operational divergences in the construction of food sovereignty / Marina Di Masso, Marta G. Rivera-Ferre, Josep-Lluís Espluga -- Consumer convergence and collective motivations for purchasing ethical products / Michael A. Long, Douglas L. Murray -- Barriers to the local food movement : Ontario's community food projects and the capacity for convergence / Phil Mount ... [et al.] -- Food policy council movement in North America : a convergence of alternative local agrifood interests? / Patrick H. Mooney, Keiko Tanaka, Gabriele Ciciurkaite -- Patchworks of sustainable agriculture standards and metrics in the United States / Jason Konefal, Maki Hatanaka, Douglas H. Constance -- Organic and non-organic farming : is convergence possible? / Bernhard Freyer, Jim Bingen -- Convergence and divergence in alternative agrifood movements / Marta G. Rivera-Ferre, Douglas H. Constance, Marie-Christine Renard.
Print version record
Keywords: Social Science -- Sociology -- Rural; Sociology: work & labour; Sociology; Food & society; Food sovereignty